Counter-trends in Educational Supervision? Policies of Inclusion as a Tool for Formal Control in Uruguay - L. Belén Espejo Villar; Mª Isabel Calvo Álvarez (Universidad Autónoma de Madrid, 2015)
The present article is an attempt to analyze inclusion policies in Uruguay as a management mechanism for the improvement of educational processes. Study of governance forms and procedures at a stage that is turning out to be crucial in retaining and attracting back an ever more important group of young people constitutes our working scenario for exploring alternative systems to market models. Despite the weaknesses and contradictions that the management structures of Uruguayan secondary education have in regard to educational policy, the development of inclusion actions opens a way of doing things that is counterpoised to the precepts of globalization and helps us to rethink new forms of pedagogical direction and management. The idea is that in contrast to the management strategies adopted in the framework of a global economy, Uruguay is interpreting them and reformulating them in another direction. This research presents the analysis of the educational possibilities offered by the government agencies in countries that, such as Uruguay, the mechanisms of power are greatly influenced by the determination that the equality policies have achieved.